Children's emerging receptive, positive orientation toward their parents in the network of early attachment relationships. Issue 5 (3rd September 2021) - An, Danming; Kochanska, Grazyna; Yeager, Nicole; Sivagurunathan, Neevetha; Praska, Rochelle; Campbell, Robin; Shin, Sung Yi
ABSTRACT: Early security plays a major role in inaugurating the child's receptive, positive orientation – a foundation for cooperative parent-child relationships and successful socialization. However, few studies have considered the association between children's attachments with both mothers and fathers and multiple aspects of children's receptive, positive orientation, or compared all four attachment groups (secure, avoidant, resistant, and disorganized). In 192 mother-child and 186 father-child dyads from community families, children's attachment was assessed at 15-17 months in Strange Situation Paradigm. Aspects of receptive, positive orientation toward each parent – positive affect, committed compliance, empathic concern, and restraint in response to parental prohibition – were observed in naturalistic laboratory contexts. Generally, securely attached children were more receptive and positive than insecure, although specific effects depended on the measure, comparison group (avoidant, resistant, disorganized), and the relationship (mother- or father-child). For positive orientation in the father-child dyads, being secure with both parents conferred a modest additional benefit.